Preventive administrative measures for protecting natural reserves: Comparative study - Hana Kasim Muhamad; Sangar Dawood Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Natural reserves face increasing challenges due to growing environmental pollution and human activities' interference. In this context, the research provides an overview of the importance of preventive measures as an effective means of preserving these vital areas. The escalating environmental pollution poses a growing threat to natural reserves, given its detrimental effects on biodiversity and the environment. This results from the weak enforcement of environmental laws due to lax administrative control authorities, coupled with the inefficiency of regulatory mechanisms in mitigating threats to natural reserves. Therefore, the research proposes a set of suggested solutions, including enhancing the enforcement of environmental laws and tightening supervision, as well as providing support and necessary resources to strengthen reserve management. Emphasizing awareness and encouraging community involvement in preserving natural reserves is also essential. This requires robust and comprehensive preventive strategies to address the escalating environmental challenges and ensure their continuity as a vital hub for biodiversity and environmental sustainability.